Hydrogen‐Bonding Amidoindoles in the Presence of Anions: An X‐ray Structure of a Receptor at the Acid–Base Half‐Equivalence that Binds an Anion. Issue 37 (9th October 2017) - Koeller, Sylvain; Lescure, Marie‐Hélène; Davies, Clotilde; Desvergne, Jean‐Pierre; Massip, Stéphane; Bibal, Brigitte
Abstract : Hydrogen‐bonding catalysts based on (thio)amidoindole moieties were evaluated in the presence of anions as potent anion receptors and/or acidic partners involved in acid–base reactions. In particular, we focused on their behavior at the acid–base half‐equivalence point in the presence of basic anions such as fluoride and benzoate salts. Among three isolated X‐ray structures, an amidoindole in the presence of fluoride and hexafluorophosphate salts formed, at the acid–base half‐equivalence point, an unprecedented sandwich complex between two receptors and a PF6 – anion. Abstract : Hydrogen‐bonding catalysts are shown to interact with anions through binding or an acid–base reaction. The X‐ray structure reveals that at the half‐equivalence point two receptors bind a PF6 – anion. HBD = hydrogen‐bond donor.